Measurement of CP violation in B 0 → D + D − and B s 0 → D s + D s − decays - Aaij, R; Abdelmotteleb, ASW; Abellan Beteta, C; Abudinén, F; Ackernley, T; Adefisoye, AA; Adeva, B; Adinolfi, M; Adlarson, P; Agapopoulou, C; Aidala, CA; Ajaltouni, Z; et al. (Springer, 2025)
A time-dependent, flavour-tagged measurement of CP violation is performed with B0→ D+D− and Bs0→Ds+Ds− decays, using data collected by the LHCb detector in proton-proton collisions at a centre-of-mass energy of 13 TeV corresponding to an integrated luminosity of 6 fb−1. In B0→ D+D− decays the CP-violation parameters are measured to beSD+D−=−0.552±0.100stat±0.010syst, CD+D−=0.128±0.103stat±0.010syst. In Bs0→Ds+Ds− decays the CP-violating parameter formulation in terms of ϕs and |λ| results inϕs=−0.086±0.106stat±0.028systrad, ∣λDs+Ds−∣=1.145±0.126stat±0.031syst. These results represent the most precise single measurement of the CP-violation parameters in their respective channels. For the first time in a single measurement, CP symmetry is observed to be violated in B0→ D+D− decays with a significance exceeding six standard deviations.